Aqueous Polymerization of Acrylonitrile and Methyl Methacrylate by Cerium(IV)-Glycine Redox System Catalysed by Bromide Ion: A Kinetic Study - Rai, S.K.; Shivakumar, K.; Sherigara, B.S. (Asian Journal of Chemistry, 2010)
Polymerization of acrylonitrile and methyl methacrylate monomers (M), initiated by a cerium(IV)-glycine redox system catalysed by bromide ion was investigated kinetically, over a temperature range of 35-50ºC in aqueous medium under inert atmosphere. The incorporation of bromide ion, with cerium(IV)- glycine redox system and rate of polymerization (Rp) has been studied at various concentrations of monomers and initiator. The polymerization exhibited a strong dependence on the concentration of bromide ion. The rate of polymerization, Rp ∝ [M][Ce(IV)]½ [AH]½[Br]½. The influence of organic solvents and temperature on the rate of polymerization has also been investigated and energy of activation was calculated. On the basis of experimental results, a suitable kinetic scheme has been proposed and a rate expression has been derived.